(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines effective pedagogical approaches to developing pragmatic competence in English language classrooms, emphasizing strategies that encourage students’ ability to use language appropriately in diverse sociocultural contexts. The study emphasizes the importance of authentic dialogue, contextualized teaching, role playing activities, discourse analysis, and technology-integrated learning. Using descriptive and comparative methods, the study evaluates the impact of these approaches on students’ communicative performance. The results of the study indicate that pragmatically oriented instruction significantly increases students’ sociolinguistic awareness, politeness strategies, speech act effectiveness, and intercultural sensitivity. The study also shows that regular exposure to real-life dialogue, interactive tasks, and reflective feedback mechanisms significantly improves students’ pragmatic development and general language proficiency.